Sports journalism : a practical introduction - Andrews, Phil, (Sportswriter), ....-; Steele, Mila, ....- (Thousand Oaks (Cal.) : Sage Publications, 2014)
He sports journalist of today needs to be well equipped for the digital age. From the challenges of minute-by-minute reporting to the demands of writing for online outlets, blogging and podcasting, sports journalism is now fully immersed in new and social media. Sports Journalism: A Practical Guide will give you the skills you need to navigate these new platforms, whilst also teaching you the basics of interviewing, reporting, feature writing for print and commentary for radio and television. This new edition now includes: New examples demonstrating the use of social media in sports journalism A new chapter on the current professional working practice of sports journalism, covering the skills required of agency and freelance journalists today A new chapter on sports public relations Expanded coverage of radio and television sports journalism, with more emphasis on commentary and multi-platform working Quotes from working journalists, offering valuable insights into the industry. This book is a complete guide to the practice of sports journalism across all platforms: print, online, radio, television and social media sites.
Keywords: Journalistiek -- Sport